Allergic respiratory disease (ARD), setting forth the basics: proposals of an expert consensus report. Issue 1 (18th May 2017) - Navarro, Ana M.; Delgado, Julio; Muñoz‐Cano, Rosa M.; Dordal, M. Teresa; Valero, Antonio; Quirce, Santiago; ,
Abstract: Background: The variability of symptoms observed in patients with respiratory allergy often hampers classification based on the criteria proposed in guidelines on rhinitis and asthma. Objectives: We assessed specific aspects of allergic respiratory disease (ARD) that are not explicitly addressed in the guidelines in order to issue specific recommendations and thus optimize clinical practice. Methods: Using the Delphi technique, 40 Spanish allergists were surveyed to reach consensus on 71 items related to ARD. Results: Consensus was achieved for 95.7% of the items. These included the following: the clinical manifestations of ARD are heterogeneous and individual airborne allergens can be related to specific clinical profiles; the optimal approach in patients with ARD is based on the global assessment of rhinoconjunctivitis and asthma; aeroallergens are largely responsible for the clinical features and severity of the disease; and clinical expression is associated with the period of environmental exposure to the allergen. Pharmacological treatment of ARD is often based on the intensity of symptoms recorded during previous allergen exposures and cannot always be administered following a step‐up approach, as recommended in clinical practice guidelines. Allergen immunotherapy (AIT) is the only option for overall treatment of respiratory symptoms using an etiological approach. AIT can modify the prognosis of ARD and should therefore be considered a valuable first‐line treatment. Conclusions: The present study highlights gaps in current asthma and rhinitis guidelines and addresses specific aspects of ARD, such as global assessment of both asthma and rhinitis or the specific role of variable allergen exposure in the clinical expression of the disease.